Cotton [a novel] - Wilson, Christopher 1946- (Harcourt, 2006)
"Wilson's winning 20th-century picaresque wanders from the Deep South to the Midwest and on to San Francisco, following its protagonist through multiple and surprising identities. If the locales exude a faint whiff of familiarity, Lee Cotton, the book's shape-shifting main character, has a body (and a mind) that keeps things interesting. Beginning life as a 'black soul in a white wrapper,' Lee leaves Mississippi after a horrific beating at the hand of a local racist. He passes for white in St. Louis, getting work as a hospital orderly. But fate has more changes in store. A freak accident and doctoring by an 'offbeat' surgeon have him embark on a new life as a woman... and then Lee's skin starts to darken. Wilson offers readers both a sharp-eyed, amusing ramble through America from the 1950s to the '70s and a critique of exclusionary identity politics. As Lee tells a heckler late in the book, "All my life I been hounded for being born the wrong color, or the wrong sex, or dating the wrong person, or living in the wrong place. We ain't what we're born. We're what we do with ourselves.'"--Publishers weekly
Keywords: Vietnamkrieg; African American families -- Fiction; Civil rights movements -- Fiction; Icelandic Americans -- Fiction; Interracial dating -- Fiction; Passing (Identity) -- Fiction; Racially mixed people -- Fiction; Spiritualism -- Fiction; Transsexuals -- Fiction; Victims of violent crimes -- Fiction; Vietnam War, 1961-1975 -- Fiction; Mississippi -- Fiction; Saint Louis (Mo.) -- Fiction; Psychological fiction; Historical fiction